دور هندسة القيمة في تخفيض التكاليف بالمؤسسات الصناعية دراسة حالة: المؤسسة الوطنية للدهن وحدة سوق أهراس - بن رجم محمد خميسي; العايبي عماد الدين (My University, 2021)
تهدف هذه الدراسة إلى بيان دور هندسة القيمة في تخفيض التكاليف على مستوى المؤسسة الوطنية للدهن وحدة سوق أهراس كعينة عن المؤسسات الصناعية في الجزائر، وبعد تحليل البيانات باستخدام برنامج Spss، توصلت الدراسة إلى أن أبرز أسباب ارتفاع التكاليف في المؤسسة يمكن معالجتها بفعالية بتطبيق هندسة القيمة، كما خلصت إلى توفر بعض المقومات التي تساهم في نجاح تطبيق هندسة القيمة وغياب بعضها الأخر، لكن يمكن للمؤسسة تدارك ذلك إذا سعت بجدية إلى تبني هذا الأسلوب. The aim of this study is to illustrate the impact of implementing value engineering in costs reduction at the national foundation of paint unit of Souk Ahras as a sample of industrial foundations In Algeria, for the purpose of collecting primary data we relied on a questionnaire distributed on the foundation employees and we used some interviews to support the interpretation of results, after analyzing the data and testing the hypotheses using the SPSS software. The study concluded that the root causes of high costs can be eliminated effectively by implementing value engineering, secondly the study discovered that the foundation has some qualifications to apply value engineering, at the same time there is an absence in some ones but it can be rectified if she seeks to implement this approach seriously.